Leveraging Functional Genomics and Engineering Approaches to Uncover the Molecular Mechanisms of Cnidarian–Dinoflagellate Symbiosis and Broaden Biotechnological Applications - Gagan Mannur; Ashley Taepakdee; Jimmy Pham Ho; Tingting Xiang (Phycology, 2025)
Functional genomics is a powerful approach for uncovering molecular mechanisms underlying complex biological processes by linking genetic changes to observable phenotypes. In the context of algal symbiosis, this framework offers significant potential for advancing our understanding of the molecular interactions between marine dinoflagellates and their cnidarian hosts, such as corals—organisms that are foundational to marine ecosystems and biodiversity. As coral bleaching and reef degradation intensify due to environmental stressors, novel strategies are urgently needed to enhance the resilience of these symbiotic partnerships. This opinion piece explores emerging directions in functional genomics as applied to coral–algal symbiosis, with a focus on uncovering the molecular pathways that govern photosynthesis and stress tolerance. We discuss the challenges and opportunities in applying functional genomics to support coral health, improve ecosystem resilience, and inform biotechnological applications in agriculture and medicine. Together, these insights posit the potential for engineered symbioses as a needed focus in mitigating biodiversity loss and supporting sustainable ecosystem management in the face of accelerating environmental change.